Kandidiasis Akut Eritematous Pada Penderita Diabetes Mellitus - Panky Hermawan; Nafi’ah; Dwi Setianingtyas; Desiana Raditya (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Oral candidiasis is an infection caused by Candida albicans. Candida infection can occur in patients with Diabetes Mellitus (DM) due to the high sugar content in the whole saliva and immunosuppresive condition of the patient. Purpose: to discuss case and treatment of acute erythematous candidiasis in patients with diabetes mellitus. Case: A 68 year old male came to RSAL dr. Ramelan Surabaya complaining of tendernes, burning and painful when eating and drinking in the left side of the tongue and. The tendernes was felt since about 8 months ago after the patient had a stroke. He had uncontrolled diabetic and hypertension.Three months later the patient felt the pain was getting worse with heartburn and pain. It was treated by given medication Nystatin drop and cefadroxil regularly until the drug ran out. During the first 2 months of treatment the tongue looked better but the pain and burning persisted. Shortly after,the tongue becomes dirty again. Case Management: Screening for diagnosis in this case include pathology anatomy examination by scrabbing the lesion, complete blood count(CBC) and blood sugar test. The result was positive hypae, normal CBC, and blood sugar level 324mg/dl. Patient was diagnosed acute erythematous candidiasis and treated with anti fungal systemic, mouthwash and topical antiseptic for oral case and reffered to interne specialist for diabetic condition. Patient was cured in 36 days. Conclusion: Controlling or eliminate predisposing factor in this case (DM) is very important in the management of acute therapy erythematous candidiasis. Comprehensive treatment for oral candidiasis in diabetic patient must include controlling predisposition factor and the right choose of anti fungal agent.